Penjatuhan Pidana Bersyarat terhadap Pelaku Tindak Pidana Menyerang Nama Baik melalui Informasi Elektronik - Utami, Erika Henidar; Amrullah, Rinaldy; Fardiansyah, Ahmad Irzal (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The crime of defamation committed through electronic information has become an increasing legal concern following the enactment of Law No. 1 of 2024 concerning amendments to the Electronic Information and Transactions Law. In practice, however, judges often impose conditional sentences instead of imprisonment, as seen in Decision No. 160/Pid.Sus/2024/PN.Kbu. This study aims to analyze the legal, philosophical, and sociological considerations underlying the imposition of a conditional sentence on perpetrators of defamation through electronic means and to examine whether such a decision aligns with the objectives of law justice, legal certainty, and expediency. This research employs a normative juridical approach using secondary legal materials, including statutory regulations, court decisions, and relevant legal literature. The data were analyzed descriptively through legal interpretation methods. The results show that the judge’s decision was based on juridical considerations that the defendant was proven to have violated Article 45 paragraph (4) in conjunction with Article 27A of the ITE Law; philosophical considerations emphasizing rehabilitation rather than mere punishment; and sociological considerations reflecting mitigating and aggravating factors. The imposition of a conditional sentence was found to be consistent with the principles of justice, legal certainty, and expediency, serving both corrective and preventive purposes.